An Acoustic Study on English Vowels Produced by Indonesian Speakers: Exploring Determining Factors and Contact Situations - Ferdinan Okki Kurniawan; Margareta Rosvita; Rintya Yuniastari (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
Compared to English varieties spoken in the inner circle (e.g., Australian English and New Zealand English), the English variety spoken in Indonesia, especially in acoustic phonetics, is still understudied. Using the Praat computer program, this acoustic study investigates the English vowel production of fifteen Indonesian females and males. The formants (F1 and F2) of their English vowel in words heed /hid/, hid /hɪd/, head /hÉ›d/, had /æ/, hod /hÉ‘d/, hawed /hÉ”d/, hood /hÊŠd/, who’d /hud/, hud /hÊŒd/, and heard /hɝd/ are measured and then compared with the vowels produced by American English speakers. Regardless of the speakers’ gender and English skill levels, the vowels [æ] and [É‘] show the most significant differences between Indonesian and American English speakers. The difference in this study is conditioned more by linguistic factors, i.e., phonetics and phonemics, than by non-linguistic factors, i.e., gender and English skill level. The findings of this study offer a discussion of how acoustic evidence resulting from language education may shed light on possible language contact situations.